(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
The Cantabrian Zone is the only area in Western Europe that contains marine successions of Kasimovian and Gzhelian (late Late Carboniferous, late Pennsylvanian) age. These successions yield fusulinoideans that are presently the subject of an in depth-study by members of a IUGS SCCS working group intending to find stratigraphic markers for the subdivision of the Carboniferous System. The youngest fusulinoidean faunas of the Cantabrian Zone are recorded in the Puentellés Formation, a succession of calcareous strata consisting of two members. The lower member is made up of reworked and re-sedimented carbonates, which form shallow turbidite deposits showing frequent lateral changes of facies, whereas the upper member corresponds to autochthonous limestones, mainly consisting of dark mudstones, skeletal wackestones and thick-bedded boundstones. Generally speaking, the lower member is late Kasimovian in age while the upper one is early Gzhelian. However, there are also a few successions of late Kasimovian age that show sedimentary facies similar to those of the upper member. The fusulinoidean assemblages from the lower member are dominated by elongated species of the genus Ferganites, which sometimes occur with Schubertella and Staffella species. Rauserites, Tumefactus, Jigulites, Quasifusulina, as well as certain Ferganites species showing obese shell, mainly appear in strata belonging to the upper member.Detailed analyses of the fusulinoideans from the Cantabrian Zone have allowed several questions related to their paleoecology, biostratigraphy, and paleobiogeography to be ascertained. First, it has been shown that the Ferganites accumulated in the strata of the lower member could have lived in near-shore and high-energy environments. The presence of some relevant forms (e. g. Rauserites cf. rossicus, and Jigulites sp.) allow a correlation between the Cantabrian successions and the standard stratigraphic units of the Russian Platform. Moreover, the composition of the fusulinoidean assemblages clearly shows the biogeographic affinities of the Cantabrian Zone with the Carnic Alps and the Central Asian regions. On the contrary, these assemblages differ greatly from those in other western Eurasian areas, such as the Russian Platform and the Donets Basin, suggesting that these areas were not well-connected with the Paleo-Tethys. Some observations give rise to relevant questions on more general aspects dealing with the latest Carboniferous fusulinoideans while yielding, at the same time, preliminary data for solving them. This is the case of the phrenotheca, an inner partition existing in some fusulinoidean shells whose functional role is still uncertain. The abundance in the Cantabrian Zone strata of Tumefactus specimens showing phrenotheca provides information for reconstructing its geometry as well as enabling speculation on its likely function. Another problematic aspect concerns the origin and distribution of the genus Triticites. It is noteworthy that this genus seems to be absent from both the Cantabrian Zone and most Eurasian areas, bringing up the question of whether the American and the Eurasian Triticites really had a common ancestor. The possibilities involved are discussed here.